Unequal and Asymmetric Internationalisation of Large Russian Cities - Ekaterina Mikhailova (EchoGéo)
To assess the degree of city’s internationalisation in Russia, the paper presents ranking conducted in 2017 of 20 large Russian regional capitals with over 600,000 inhabitants on the basis of 13 indicators. The paper concludes that, by 2017, Yekaterinburg has become a confident leader of internationalisation while Novosibirsk, Kazan, Nizhny Novgorod, Krasnodar and Rostov-on-Don stand out as other highly internationalised large Russian cities. At the same time, 14 out of 20 Russian regional capitals in the sample demonstrate asymmetrical or weak internationalisation. Besides, the paper puts forward the electronic internationalisation index as a tool for qualitative benchmarking city's international online marketing activities.